1998
DOI: 10.1046/j.1365-2923.1998.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Video recording feedback: a feasible and effective approach to teaching history‐taking and physical examination skills in undergraduate paediatric medicine

Abstract: Medical educators have always recognized the need to teach and train medical graduates and undergraduates the skills of conducting a consultation. Several authors have established the efficacy of using constructive feedback on videotape of each student's interaction with a patient to teach and enhance such skills. This study reports 'students' perceptions' of the feedback process used in the Junior Paediatric Clerkship at the Faculty of Medicine of the United Arab Emirates University. An unexpected 73% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 15 publications
3
46
2
11
Order By: Relevance
“…Different educational methods have been adopted: role playing with peers or simulated patients, discussion, video recording or real patient encounters (Kaplan et al 1997;Rees et al 2004;Deveugele et al 2005;Lane & Rollnick 2007;Gillard et al 2009). Numerous studies have focused on the differential effect of educational approaches that foster medical students' consultation skills development (Cline & Garrard 1973;Cassata et al 1976;Maguire et al 1978;Carroll & Monroe 1979;Brown & O'Shea 1980;Manahem et al 1984;Scheidt et al 1986;Paul et al 1998; Practice points . Conducting a consultation is a complex skill for undergraduate medical students, and paying attention to both the cognitive and the motivational side of a consultation setting is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Different educational methods have been adopted: role playing with peers or simulated patients, discussion, video recording or real patient encounters (Kaplan et al 1997;Rees et al 2004;Deveugele et al 2005;Lane & Rollnick 2007;Gillard et al 2009). Numerous studies have focused on the differential effect of educational approaches that foster medical students' consultation skills development (Cline & Garrard 1973;Cassata et al 1976;Maguire et al 1978;Carroll & Monroe 1979;Brown & O'Shea 1980;Manahem et al 1984;Scheidt et al 1986;Paul et al 1998; Practice points . Conducting a consultation is a complex skill for undergraduate medical students, and paying attention to both the cognitive and the motivational side of a consultation setting is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Through feedback, students recognize areas of deficiency in their knowledge and skills and seek to remedy these. Studies have shown that feedback improve interview and communication skills (Verby 1976), physical examination skills (Paul et al 1998), technical skills (Kardash & Tesler 1997), problem based learning, team building (Paikh et al 2001) and personal and professional behaviours (Rees & Shepherd 2005). Yet, despite its importance, students do not always receive the desired formative feedback during the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmalarda, klinik performansı ile ilgili geribildirim alan öğrencilerin bu deneyimleri ile ilgili olumlu tutum bildirdikleri (18,(20)(21)(22), öğrencilerin uygun şekilde öykü alma ve yeterli fizik muayene yapmayı öğrenmek için güdülendikleri belirtilmektedir (22). Ayrıca çalışmalar geribildirimin öğrenci performansı üzerinde önemli etkisi olduğunu ve daha fazla öğrenme-ye teşvik ettiğini göstermektedir (21,23).…”
Section: Introductionunclassified